Application of 3D Printing in Interior Design and Furniture - Shaimaa Mahran (Journal of Architecture, Art & Humanistic Science, 2019)
3D printers are a scientific and technological revolution , not only in modern technology field, but also in various areas of life. There is no field that the printer had not an effect there. It is technology to medicine, engineering, education, science, dentistry, down to interior design and furniture.This research explains concept of 3D printing, and its application in interior design and furniture, and its role in modern design trends, and explain the differences and similarities between them and the techniques of manufacturing three-dimensional forms using the computer.Introduction Introduction:3D Printing is an innovative technology that enables people to create models through a digital model. Where the three-dimensional printing is known as manufacturing plus additive manufacturing. A process that involves taking the digital model of the stereoscopic design, translating it into a series of horizontal slices in the language of the machine, and printing it by adding successive layers and very accurate (not exceeding the thickness of parts of the millimeter) of materials until the 3D object is created using a number of different techniques .When we talk about 3D printers, we are not talking about a distant future, but talking about a recent past. The concept of holographic printing was first introduced in 1980, while the first 3D printer was invented in 1984 by Chuck Hull, the American inventor of this revolutionary technology. However, three-dimensional printers were not available for commercial consumption until the beginning of the year .The implementation of three-dimensional printing technology plays a key role in transforming fictional and innovative forms into works and products on the ground, with meticulous precision and timeliness.The field of interior design and furniture is one of the most important areas of applying innovative ideas and adapting them to the service of human beings. This offers wider opportunities for utilizing 3D printing techniques.